ANALISIS KAPASITAS ADSORPSI SILIKA DARI PASIR PANTAI PANJANG BENGKULU TERHADAP PEWARNA RHODAMINE B - Fitri Esa Madina; Rina Elvia; I Nyoman Candra (University of Bengkulu, 2017)
[ANALYSIS OF SILICA ADSORPTION CAPACITY FROM THE SAND OF PANTAI PANJANG BENGKULU AGAINST RHODAMINE B DYES ] This research was aimed to study the adsorption capacity of synthetic silica on Rhodamine B dyes. Synthetic silica was obtained from the sand of Pantai Panjang Bengkulu by alkali fusion method using KOH at 360 °C for 4 hours in furnace to obtain potassium silicate crystals (K2SiO3). The crystals were then added 500 mL aqua DM, stirred and sterilized for 24 hours folloed by filtered. The filtrate was dropped with 10 M HCl solution until the pH of filtrate solution reached at 1 to 2 and formed a silent white gel for 24 hours. Moreover, the gel was filtered with filter paper and washed with aqua DM until pH is neutral and free from KCl, and dried in an oven at 60 °C for 18 hours. The obtained silica powder is then smoothed with mortar and weighed. The adsorbent of Rhodamine B dyes using the synthetic silica powder was performed on pH variation at 2, 3, 4, 5, 6, and 7 , and variation of contact time at 10, 20, 30, 40, 50, and 60 min. The results showed that the optimum condition of adsorption of Rhodamine B by silica from Pantai Panjang sand occured at optimum pH 2 and optimum contact time 20 minutes; with adsorption capacity of 4.95 mg / g and 4.79 mg/g; and with adsorption efficiency of 99.00% and 95.89%.